1982
DOI: 10.1136/bmj.284.6317.706
|View full text |Cite
|
Sign up to set email alerts
|

Non-smoking: a feature of ulcerative colitis.

Abstract: We suggest that chlormethiazole may have caused dysphagia by a direct action on the central mechanisms concerned in swallowing. Most reports of the adverse effects of this drug concentrate on the problems of drug abuse and addiction,3 and dysphagia has not been reported as a side effect. There have been some reports of dyspepsia, nausea, and vomiting related to the acidity of the tablets.4 This is unlikely to have been important in the present case, however, since no reflux was detected during overnight record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
3
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(116 citation statements)
references
References 3 publications
5
106
3
2
Order By: Relevance
“…[1][2][3][4] Paradoxically, UC appears to be predominantly a disease of ex-smokers and nonsmokers. 2, First noted by Samuelsson in 1976 25 and confirmed by Harries, Baird and Rhodes in 1982, 26 it was observed that there was a distinct lack of current smokers in a cohort of UC patients, compared with that of a group of matched control subjects. Since then, numerous studies of the relationship between smoking and UC have confirmed this observation and demonstrated that smoking not only appears to protect against the development of UC, but in fact ameliorates the clinical course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Paradoxically, UC appears to be predominantly a disease of ex-smokers and nonsmokers. 2, First noted by Samuelsson in 1976 25 and confirmed by Harries, Baird and Rhodes in 1982, 26 it was observed that there was a distinct lack of current smokers in a cohort of UC patients, compared with that of a group of matched control subjects. Since then, numerous studies of the relationship between smoking and UC have confirmed this observation and demonstrated that smoking not only appears to protect against the development of UC, but in fact ameliorates the clinical course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The link between smoking and (IBD) was first made in 1982 when Harries et al [6] noticed a low proportion of ulcerative colitis patients were smokers. Two years later a case-control study by Somerville et al [7] reported that the relative risk of developing Crohn's disease was 4.8 in those who smoked before disease onset, and 3.5 for those with a current smoking habit.…”
Section: Introductionmentioning
confidence: 99%
“…The first report on non-smoking as a risk factor in UC was published in 1982, and several more have confirmed this observation [84]. Smoking is associated with lower onset risk, fewer hospitalizations, lower relapse rate and decreased need for colectomy in UC [85][86][87].…”
Section: Ucmentioning
confidence: 84%